2007
DOI: 10.1111/j.1742-4658.2007.05732.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of cholinesterase inhibition by inorganic mercury

Abstract: The poorly known mechanism of inhibition of cholinesterases by inorganic mercury (HgCl2) has been studied with a view to using these enzymes as biomarkers or as biological components of biosensors to survey polluted areas. The inhibition of a variety of cholinesterases by HgCl2 was investigated by kinetic studies, X‐ray crystallography, and dynamic light scattering. Our results show that when a free sensitive sulfhydryl group is present in the enzyme, as in Torpedo californica acetylcholinesterase, inhibition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(48 citation statements)
references
References 58 publications
(61 reference statements)
2
45
1
Order By: Relevance
“…This may be due to the absence of a free sulfhydryl group. According to Frasco et al (28), when a free sulfhydryl group is absent in the enzyme (Drosophila melonogaster acetylcholinesterase and human serum butyrycholinesterase) inhibition by mercury will occur in the millimolar range, while in the presence of a free sulfhydryl group (Electrophorus electricus), the inhibition will only require a micromolar concentration (28). It is possible that the inhibitory effects of metals on venom acetylcholinesterase are due to the formation of inactive enzyme aggregate (29).…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the absence of a free sulfhydryl group. According to Frasco et al (28), when a free sulfhydryl group is absent in the enzyme (Drosophila melonogaster acetylcholinesterase and human serum butyrycholinesterase) inhibition by mercury will occur in the millimolar range, while in the presence of a free sulfhydryl group (Electrophorus electricus), the inhibition will only require a micromolar concentration (28). It is possible that the inhibitory effects of metals on venom acetylcholinesterase are due to the formation of inactive enzyme aggregate (29).…”
Section: Discussionmentioning
confidence: 99%
“…These two regions are mutually responsive to ligand-dependent conformational changes and it was proposed by other authors that occupancy of peripheral site induces movements in the loop which in turn modify the orientation of the key tryptophan residue present in the choline binding site of the active center [23,[38][39][40]. It suggested that conformational alterations from the binding of Hg 2+ to the loop and the other three peripheral mercury-binding sites reported by Frasco et al [10] could allosterically be transmitted to the choline binding locus of the active center interfering in substrate binding and, inversely, the substrate binding to peripheral (substrate inhibition site) and active sites, in increasing concentrations, could hinder Hg 2+ binding to AChE loop since the position of residues in this region undergo a modification becoming more exposed to the solution after peripheral site occupancy [39,40]. The ion would be displaced from the loop and not from the active center therefore mimicking the behavior of a competitive inhibitor.…”
Section: +mentioning
confidence: 97%
“…Several studies reported inhibition of AChE activity by ions [9][10][11]. AChE activation by Ca 2+ , Mg 2+ , Al 3+ has also been reported [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations